Indigenous ornamental fishes of west Bengal - Basu, Abhisek; Dutta, Dibyendu; Banerjee, Samir (Recent Research in Science and Technology, 2013)
Ornamental fishes are attractive colourful fishes of peaceful nature that are kept as pets in aquarium for recreation purpose. Ornamental fish keeping is the second most popular hobby next to photography. And the ornamental fish industry is one of the most booming one among the World; India having a good share of it. India is blessed with a great resource of different natural ornamental fishes. West Bengal is also sanctified with a wide range of indigenous ornamental fishes of biological as well as commercial importance. Due to lack of information and proper conservation strategy many of them are on the verge of extinction. In the present study, different rivers and water bodies of all the districts of West Bengal have been surveyed thoroughly for natural ornamental fishes. A total number of 70 indigenous ornamental fish species belonging to 45 genera, 30 families and 9 orders were collected and identified during the survey period. Among all the collected fishes order cypriniformes shows the maximum species variation, followed by perciformes and siluriformes. The study shows that a lot of the available ornamental ichthyofauna are endemic to some region and needed to be conserved. Among the fish specimen available many have a huge commercial value. But habitat destruction, unregulated fishing practice, water pollution, lack of proper awareness and introduction of exotic fishes are some potent reasons of declining fish population of this region.